An Overview of Precision Irrigation Systems Used in Agriculture - Plaščak, Ivan (Array, 2021)
The introduction of precision agriculture increased the efficiency of plant production, while simultaneously reducing the production cost. Precision irrigation can be considered as the combination of sensors, computer software and irrigation systems. Precision irrigation has reduced water consumption and increased yields, and thus increased economic profits. The development of new crop monitoring technologies in precision irrigation has been made possible by the imaging and analysis of real-time crop condition data. The aim of this study was to describe the present state and possibilities of precision irrigation in practice in the EU and Croatia. An overview of the current precision irrigation technologies, as well as its adaptive management to the decision-making in agricultural water management, represents a fundamental basis for future practical studies in precision irrigation.